2015
DOI: 10.23960/jat.v3i1.1964
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH PEMBERIAN BORON TERHADAP PERTUMBUHAN DAN PRODUKSI DUA VARIETAS MELON (Cucumis melo L.) PADA SISTEM HIDROPONIK MEDIA PADAT

Abstract: Melon (Cucumis melo L.) merupakan tanaman hortikultura dari famili Cucurbitaceae.  Pemberian unsur hara boron yang tepat dan sesuai, Serta budidaya melalui metode hidroponik di dalam rumah kaca diharapkan mampu menunjang pertumbuhan dan meningkatkan produksi buah.  Penelitian bertujuan mengetahui perbedaan respons pertumbuhan dan produksi melon, konsentrasi boron terbaik dan pengaruh interaksi antara konsentrasi boron dengan varietas terhadap pertumbuhan dan produksi pada sistem hidroponik. Penelitian dilaksan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This is in accordance with an opinion, the element Boron plays a role in plant development, especially in the process of transporting sugar and encouraging tissue meristematic activity, so that there is a role for Boron in the process of cell division and transporting sugar to plants during fruit development [11]. The application of Boron in hydroponic cultivation of Aramis variety of melon showed the best response at a concentration of 0.8 ppm [12]. This result also showed that adding Boron fertilizer can increasing the seed weight.…”
Section: Resultssupporting
confidence: 88%
“…This is in accordance with an opinion, the element Boron plays a role in plant development, especially in the process of transporting sugar and encouraging tissue meristematic activity, so that there is a role for Boron in the process of cell division and transporting sugar to plants during fruit development [11]. The application of Boron in hydroponic cultivation of Aramis variety of melon showed the best response at a concentration of 0.8 ppm [12]. This result also showed that adding Boron fertilizer can increasing the seed weight.…”
Section: Resultssupporting
confidence: 88%
“…flowers, it is very appropriate to prevent flower and fruit loss, can stimulate root growth so that it causes maximum absorption of nutrients in the soil, and stimulates growth and improves plant health so that it is not susceptible to pests and diseases, while magnesium (Mg) functions in the photosynthesis process ( because it helps the formation of chlorophyll which is important in photosynthesis) also supports plant permeability so that it helps the respiration process; increases plant resistance or immunity against pests and diseases; formation of nutrients in plants (sugars, carbohydrates, fats, proteins and oils); increases plant productivity because it can prevent the fall b flowers and fruit. Stated that boron (B) is one of the micro elements that is needed in small amounts but if it is deficient it will affect the production and survival of plants [27]. Boron functions to strengthen cell walls, increase protein synthesis and improve fruit quality.…”
Section: Resultsmentioning
confidence: 99%
“…Boron also plays a role in carbohydrate transport from photosynthesis, thereby improving photosynthetic efficiency and ultimately increasing fruit production (Ai, 2022). The fruit production is indicated by fruit weight, which is determined by fruit diameter and flesh width (Rahma et al, 2015).…”
Section: Growth and Production Of Cucumbermentioning
confidence: 99%
“…Boron also plays a role in carbohydrate transport from photosynthesis, thereby improving photosynthetic efficiency and ultimately increasing fruit production (Ai, 2022). The fruit production is indicated by fruit weight, which is determined by fruit diameter and flesh width (Rahma et al, 2015). Therefore, the addition of boron at various rates can lead to increased cucumber fruit production due to its multiple effects on plant physiology and metabolism.…”
Section: Growth and Production Of Cucumbermentioning
confidence: 99%